In silico design of novel recombinant antigens containing immunologically relevant regions of wild-type and escape mutant variants of HBsAg - Yeshwas Abite Workneh; Desye Melese Sisay; Abebaw Fekadu; Abraham Tesfaye Bika; Alemu Tekewe Mogus; Tesfaye Sisay Tessema (PLoS ONE, 2026)
Hepatitis B virus (HBV) contributes substantially to liver cancer, related mortality, and liver transplantation worldwide. The small hepatitis B surface antigen (HBsAg), particularly its major hydrophilic region (MHR) and the “a” determinant, is the primary target of serological diagnostics. However, escape mutant amino acid variants (EMAVs) within this region may reduce diagnostic specificity and sensitivity. In this study, publicly available HBsAg sequences were analyzed to determine the prevalence of EMAVs circulating in Ethiopia. We computationally designed three region-specific recombinant antigens (MeRPYS1, MeRPYS2, and MeRPYS3) by incorporating both wild-type and prevalent EMAV sequences. Linear and conformational B-cell epitopes, as well as T helper cell epitopes, were predicted for each antigen. Homology analyses were also performed to assess similarity to host proteins. Secondary and tertiary structures of the antigens were predicted to generate theoretical molecular models. Molecular docking analyses were performed to explore putative interaction patterns between each designed antigen and an anti-HBsAg-specific antibody. The predicted antigen–antibody complexes were further examined using molecular dynamics (MD) simulations to assess their theoretical stability and behavior over time. The resulting simulations provide predictive computational insights into possible antigenic features and interaction tendencies of the designed constructs. These findings are intended to generate testable hypotheses and should be interpreted cautiously, as the study is limited to in silico analyses and requires experimental validation.